THE ROLE OF SCHOOL TEACHERS IN ENHANCING THE ECOLOGICAL CULTURE OF THE POPULATION (American Journal of Pedagogical and Educational Research, 2024)
The article provides information about the role of school teachers in teaching natural sciences to school teachers and understanding the priceless importance of nature, preserving and protecting it, ecological culture and increasing the ecological culture of the population, instilling love for nature conservation.